Blood Osmolytes of Fish Notothenia coriiceps, Chaenocephalus aceratus, Parachaenichthys charcoti caught near the Argentine Islands, Antarctica - Savytskiy, Olexandr L.; Danylenko, Kostiantyn M.; Lutsenko, Dmytro G. (Problems of Cryobiology and Cryomedicine, 2017)
Â  Probl Cryobiol Cryomed 2017; 27(4): 367-371